Kinematics and kinetics of squats, drop jumps and imitation jumps of ski jumpers - Pauli, C.; Keller, M.; Ammann, F.; Lorenzetti, S. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to find objective factors in athleticism training which influence the performance of ski jumpers on the hill. Therefore, barbell squats, drop jumps and imitation jumps were measured in a laboratory environment for ten ski jumpers. Force and motion capture data was gathered and forces, velocities as well as an index for the knee valgus were calculated. The results show that especially for the imitation jumps there is a good correlation of the take-off velocity with the performance on the hill. What surprised more is that the more the athletes tended to a knee valgus during all measured movements, the worse the performance. Therefore, athleticism training should concentrate more on improving the knee stability.